THE ESSENCE OF THE DEGREEONYY OF SYNONYMS FROM THE STANDPOINT OF THE FUNCTIONAL-SEMANTIC APPROACH (Conferencea, 2022)
This article represents the development of a functional-semantic model of the language, aimed at the analysis of degreeonymy of synonyms and the functioning of units that enter into synonymous relations. Functional synonymy is subordinate clauses and synonymous constructions with degreeonymy forms and some other types of syntactic synonymy.